Dada a função f: R -> R, definida por f (y) = y2 + 7, determina o valor de f (3) - f (0) + f (2).
A) 13
B) 24
C) 27
D) 20
E) 19
Anexos:
![](https://pt-static.z-dn.net/files/de0/2daeb80f22f1b0fbed9490a4426f15f7.jpg)
Soluções para a tarefa
Respondido por
2
Resposta:
20
Explicação passo-a-passo:
f(3)= 3²+7=9+7=16
f(0)=0²+7=7
f(2)=2²+7=4+7=11
f(3) - f(0) + f(2)
16-7+11= 20
Perguntas interessantes
Física,
8 meses atrás
Geografia,
8 meses atrás
Física,
8 meses atrás
Informática,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
1 ano atrás